Comparison of clinical course of Acute Biliary and Non-Biliary Pancreatitis - Abhishek Bhattarai; Pragya Devkota; Bishu Prasad Kandel; Bikal Ghimire; Prasan Bir Singh Kansakar; Ramesh Singh Bhandari; Kishor Kumar Tamrakar; Palaswan Joshi Lakhey; Parshuram Mishra; Yogendra Prasad Singh; Pradeep Vaidya; Keshaw Prasad Singh (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Incidence of acute pancreatitis (AP) varies in different parts of the world. The published data are mainly based on retrospective analysis of hospital admissions, which show that there are considerable geographical differences in the incidence rate. There are also regional divergences with regard to the etiology, and its impact on morbidity and mortality. Therefore, we compare the clinical course of acute biliary and non-biliary pancreatitis at the Tribhuvan University Teaching Hospital (TUTH) as well as we compare the morbidity and mortality and duration of hospital stay in these groups.